Oral and Written Traditions of Buginese: Interpretation Writing Using the Buginese Language in South Sulawesi - Yusuf, Muhammad; Suardi Wekke, Ismail (International Journal of Psychosocial Rehabilitation, 2019)
The uniqueness of the Buginese tribe is in the form of its oral and written traditions that go hand in hand. Oral tradition is supported by the Lontarak Manuscript which consists of LontarakPasang, Attoriolong, and Pau-pau riKadong. On the other hand, the Buginese society has the Lontarak script, which supports the written tradition. Both of them support the transmission of the knowledge of the Buginese scholars orally and in writing. This study would review the written tradition of Buginese scholars who produce works in the forms of interpretations using the Buginese language. They have many works in bequeathing their knowledge, which is loaded with local characters, including the substance and medium of the language. The embryonic interpretation began with the translation works and rubrics. Its development can be divided based on the characteristics and the period of its emergence. The First Period (1945 – 1960s) was marked by copying interpretations from the results of scholars’ reading. The Second Period (the mid-1960s – 1980s) was marked by the presence of footnotes as needed, translations per word, simple indexes, and complete interpretations with translations and comments. The Third Period (the 1980s – 2000s) started by the use of Indonesian and Arabic languages and the maintenance and development of local interpretations in Buginese, Makassarese, Tator, and Mandar. The scholar adapts this development while maintaining local treasures.